Review of Strategies and Policies for Participation in Global Value Chains - Sourish Dutta (Cambridge Open Engage, 2024)
This article reiterates the importance of understanding and addressing the strategic inquiries and potential responses in the context of global value chain (GVC) participation. Policymakers must address these crucial matters to engage in GVCs effectively. Governments aspiring to participate in GVCs must focus on determining which tasks to prioritise and exploring various forms of GVC governance. The challenges and opportunities of establishing top-notch GVC connections and fostering a favourable environment for foreign assets are significant for countries looking to integrate into GVCs. While navigating power dynamics and supply chain risks, these efforts can attract suitable foreign investors, enhance market connectivity, and develop high-quality infrastructure and services, all of which can lead to significant economic growth and development. The potential benefits of GVC participation are vast, and by understanding and addressing the strategic inquiries and possible responses, policymakers can take control of the situation and pave the way for a prosperous future.
Keywords: F13; L52; O24; O25; 330; Global Value Chains; Trade Policy; Industrial Policy; International Political Economy